Subacute Sclerosing Panencephalitis (Journal of Dhaka National Medical College & Hospital, 2021)
Subacute sclerosing panencephalitis (SSPE) is a late complication of measles virus infection. It presents with psychiatric manifestations, progressive dementia,myoclonic jerks and other focal neurological signs. The diagnosis is based characteristic clinical manifestations, presence of charac- teristic periodic EEG discharge and demonstration of raised antibody titer against measles in plasma and CSF. In our case, patient presented with myoclonic jerk, characteristic EEG and raised level of antibody in CSF.J. Dhaka National Med. Coll. Hos. 2021; 27 (02): 41-42